British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages 258 APRIL 30, 1938 REPORT OF COUNCIL SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL "The importance of the service to the national endeavour towards raising the level of the health of the people as a whole and increasing the value of the life and capacity of each citizen can scarcely be over-estimated. The medical practitioners who provide the service, by virtue of their opportunities for the early detection of disease in the individual, form the first line of defence against communal disease; and they provide also in most cases the best instrument for the prompt application to individuals of those preventive measures and improved methods of treatment which science puts at our disposal. "The year 1933 saw the 'coming of age' of the service, and on appropriate occasions during the year much was said in celebration of the event by public men who had been or were concerned with the origin of its scheme in its various aspects. These utterances showed remarkable unanimity in their praise of what the service has accomplished. No one suggested that the scheme was or is immune from criticism, or incapable of improvement. No human scheme is, and nowhere is the need for the application of every energy towards steady improvement recognized more clearly than among those directly concerned in administering and working the scheme. But no public speaker proposed that insurance should be stopped or curtailed, and no one had the least doubt that the medical service given to the insured population to-day is not only vastly superior to the service given to the same class of people before the introduction of national health insurance, but that the improvement since its inception has been steady and continuous." 44. Although different views have been expressed as to the best method of financing an extended service — and it is not within the province of the medical profession to express a view on this subject — it is widely accepted that, for a number of reasons, the most practicable and desirable method of providing the complete general practitioner medical service is by the extension and amplification of the type of medical service now given under the National Health Insurance Acts. 45. The views of a departmental committee, of an independent body, and of the medical profession agree. The Departmental Committee on Scottish Health Services (1936): "The statutory provision for general medical attendance should be extended to include dependants of insured persons and, so far as practicable, others in similar economic circumstances, and all statutory provision for general medical attendance should be co-ordinated." PEP (1937): "We consider that the making universal of general practitioner services is one of the most urgent conditions of an adequate national health policy, and the most practicable way of securing this object is by a reform and extension of national health insurance." The British Medical Association (1929): "That medical benefits of the present National Health Insurance Acts should be extended so as to include the dependants of all persons insured thereunder and entitled to medical benefit." 46. The Availability of the Service. — Although the dependants of persons at present insured constitute the great majority of those in the same economic class not covered by the existing service, there remain a considerable number of persons not included in the group. Included in this number are persons over 70 in receipt of non-contributory pensions, those in independent business, and those in uninsurable occupations with incomes below a certain limit, together with their dependants, and the dependants of those in the Defence Services who at present receive only maternity benefit. It would be desirable to include these groups in any extended service in order that it may be available to everyone in the economic group within the £250 income limit. The problem of the inclusion of those in independent business in a scheme on the lines of the existing one — that is, in a scheme of compulsory insurance to which payments are made by the insured person, the employer, and the State — although a difficult one, should be soluble on the basis of contributions as from the insured person and the State. The remainder of this group at present depends largely on the public assistance medical service for its domiciliary medical care. 47. It is clearly undesirable that the method of medical provision in the case of the poorest section of the population should differ from that enjoyed by the community generally. Free choice of doctor should not be denied on purely social grounds. In a number of areas public assistance domiciliary services have been reorganized within the framework of the existing law so as to secure free choice of doctor and the employment of all available general practitioners in place of the selected part-time or whole-time district medical officer. New legislation is required, however, to put this service on a proper basis. 48. When legislation is introduced to extend national health insurance, it should at the same time be made possible to bring to an end this anomalous situation. The method of doing this must depend on the method of financing the extended scheme as well as on the system of administrative control adopted. If, for example, the local authority becomes the local administrative authority for all health services and the contributory basis is retained, the transfer of money from central or local funds to those of the extended service, in respect of persons from whom no contributions are received, would appear to be the basis of the practicable solution and to present little difficulty. 49. Doctor and Patient. — It is appropriate to refer here to certain general features of medical service to which the medical profession, in the interests of the public, attaches great importance. The success of the present national health insurance service is due, in no small measure, to the general acceptance of the principles: (а) That the interposition of any third party between the doctor and the patient should be as limited as possible. (b) That, as far as is possible, responsibility should be placed on the medical profession itself for the control of the purely professional side of the service, for the maintenance of the highest possible quality of service, and for the discipline of practitioners taking part. (c) That the organized medical profession should be freely consulted on all professional matters by those responsible for the administrative and financial control of the service. 50. In the first place, the relations between doctor and patient are so intimate that both doctor and patient rightly resent any outside interference. Such interference is bad for the doctor and worse for the patient. It is bad for the doctor because his whole training and the traditions of his profession tend to foster the idea of personal responsibility, and this can be undermined only at the risk of rendering the doctor less efficient. It is worse for the patient, because, ex hypothesi, he or she is a sick person whose cure depends very largely on complete confidence in the doctor, and this confidence is built up to a great extent on psychological factors which are disturbed by the intrusion of outside agencies. The poorer sections of the community should have the same consideration in this matter as is demanded as a matter of course by the more wealthy sections of the community. The patient should be able to feel that the doctor is his doctor, acting whole-heartedly and independently on his behalf, and without other relationships which tend to become paramount. 51. The experience gained from the national health insurance system has shown that the interests of the public are best served in any organized medical service by putting as much responsibility as possible on the doctors giving the service — responsibility, that is, for the quality of the service and for its smooth working. There are no severer critics of delinquent doctors than their own colleagues invested with the control of purely professional affairs. And there is no surer way of securing an efficient service than to enlist the active interest of 292/847/1/60